2021
DOI: 10.21203/rs.3.rs-380210/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sparse Channel Estimation for DCO-OFDM VLC Systems in the Presence of Clipping Noise

Abstract: In this paper, a new iterative channel estimation algorithm is proposed that exploits channel sparsity in the time domain for DC-biased optical orthogonal frequency division multiplexing OFDM (DCO-OFDM) systems in indoor visible light communications (VLC) in the presence of a clipping noise. A path-based channel model is used, in which the channel is described by a limited number of paths, each characterized by a delay and channel gain. Making use of the pilot symbols, overall sparse channel tap delays and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In [E. B. Bektas and E. Panayirci 2021], channel sparsity is exploited to VLC and DCO-OFDM in attendance of the noise clipping. The simulation results illustate the converges of algorithm in the top of two iterations and that leads to enhance MSE and BER performance, outperforming CE algorithms, having no clipping noise mitigation capability.…”
Section: Introductionmentioning
confidence: 99%
“…In [E. B. Bektas and E. Panayirci 2021], channel sparsity is exploited to VLC and DCO-OFDM in attendance of the noise clipping. The simulation results illustate the converges of algorithm in the top of two iterations and that leads to enhance MSE and BER performance, outperforming CE algorithms, having no clipping noise mitigation capability.…”
Section: Introductionmentioning
confidence: 99%
“…Also, using ACO-OFDM decresed the BER than that done in DCO-OFDM. In Bektas and Panayirci (2021), channel sparsity exploited the DCO-OFDM for indoor VLC systems with a clipping noise. The simulation results showed that the algorithm converges in a maximum of two iterations and that gets excellent MSE and BER performance, outperforming CE algorithms, having no clipping noise mitigation capability.…”
Section: Introductionmentioning
confidence: 99%